2009
DOI: 10.28945/1072
|View full text |Cite
|
Sign up to set email alerts
|

E-Portfolios for Integrated Reflection

Abstract: E-portfolios have been widely used in the education community. Currently, e-portfolios are viewed mostly as a tool of assessment and showcase, but less as a tool of active learning. This paper proposes an ontological model that specifies a generic organizational structure of eportfolios in the integrated reflection context. An example of design artifact of ontology of eportfolios is used to illustrate the concepts of the development and use of e-portfolios for active learning through reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…This included asking questions that may be outstanding and potentially being provided an answer to the question in either the next lecture or by the tutor who marked the weekly reflection. The results are in line with the previous literature regarding the strengths of ePortfolio systems for assessment purposes [52] (p. 5), and have furthered the understanding into the effective application of ePortfolios for integrated reflection practice, which was presented as a challenge for students in a study by Wang (2009) [6].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This included asking questions that may be outstanding and potentially being provided an answer to the question in either the next lecture or by the tutor who marked the weekly reflection. The results are in line with the previous literature regarding the strengths of ePortfolio systems for assessment purposes [52] (p. 5), and have furthered the understanding into the effective application of ePortfolios for integrated reflection practice, which was presented as a challenge for students in a study by Wang (2009) [6].…”
Section: Discussionsupporting
confidence: 88%
“…Chalk & Wire (https://www.campuslabs.com/chalk-and-wire/ (accessed on 29 April 2021)) is an assessment-oriented ePortfolio system that has applicability to all disciplines and supports the users' academic, career development and job seeking needs thanks to its wide array of tasks, for example course work presentation, external fieldwork assessment, secure resume and downloadable portfolios [5]. As a pioneer ePortfolio system, Chalk & Wire was widely used in Canada and the United States [6], especially in higher educational institutions where it was officially implemented campus-wide for reflection and assessment in various programs and courses [7][8][9]. In Australasia, however, this viable and powerful assessment ePortfolio system was under adopted.…”
Section: Chalk and Wire Eportfolio Systemmentioning
confidence: 99%
“…A portfolio's support for reflective thinking is its most defining pedagogical feature (Ellsworth, 2002). Research has shown that the process of constructing an e-portfolio stimulates students to engage in reflective thinking and subsequently self-evaluate and consider their learning (Cambridge, 2010;Wade, Abrami, & Sclater, 2005;Wang, 2009). The e-portfolio can also be a powerful tool to 1) promote learning (including learning from the process of assembling the portfolio); 2) improve critical thinking and content areas; 3) record accomplishments in an educational context held by the students for their own use; 4) assess long term, ongoing, authentic evaluation, and self-evaluation and self-reflection, and 5) provide evidence of continuous development (Orland-Barak, 2005;Pelliccione & Raison, 2009).…”
Section: Background E-portfoliosmentioning
confidence: 99%
“…The main reason for this practice is to promote a learner-centered approach and more active learning experiences and pedagogical changes in higher education (Joyes, Gray & Hartnell-Young, 2010). In teacher training programs, eportfolios are formed as "living-learning experiences" by prospective teachers as an evidencebased approach (Wang, 2009).…”
Section: Introductionmentioning
confidence: 99%